Pengaruh receivable turnover dan gross profit margin pada current ratio pt. telekomunikasi indonesia, tbk - Nunung Herawati; Wulandari Wulandari (Forum Kerjasama Pendidikan Tinggi, 2021)
This study aims to determine the effect of receivable turnover and gross profit margin on the current ratio. The number of samples for 5 years with the sampling technique used was purposive sampling technique. Data analysis method used is descriptive analysis, which describes the problem in such a way about the events and behavior of the object being studied, collecting data, compiling, analyzing and interpreting it objectively. Hypothesis testing uses the two-party t test and F. The results of the analysis show that receivable turnover and gross profit margin variables significantly influence the current ratio at PT. Telekomunikasi Indonesia, Tbk in the period 2011 to 2018. In the period of 2011 to 2018 showed gross profit margin did’t have a significant effect partially on the current ratio at PT. Indonesian Telecommunications. Partially receivable turnover has no significant effect on the current ratio so Ha is rejected and Ho is accepted